The Effectiveness Of Tax Collection And Vehicle Tax Arrears Collection At The Sentani Samsat Office In Jayapura District - Koapaha , Hartiny Pop; Wahamuri, Arvy (Paradoks : Jurnal Ilmu Ekonomi, 2024)
This study aims to determine the effectiveness of vehicle tax arrears collection and the effectiveness of tax collection at the Sentani Samsat Office, Jayapura Regency in 2017-2022, as well as factors that hinder collection and government efforts to increase vehicle tax revenue. The research method used is a descriptive method with a qualitative approach. The results showed that vehicle tax revenue was very effective because it had reached the target with the highest achievement rate of 109.07% in 2017, but the realization of revenue in 2021 had not reached the target which was only 91.01% due to the impact of the Covid-19 pandemic. Meanwhile, the collection of tax arrears is considered less effective because the realization of achievement is still below 80%. Factors inhibiting vehicle tax collection are the lack of awareness and understanding of taxpayers about the provisions of tax payments, mismatches in taxpayer data, and transfer of vehicle ownership without transferring the name. To increase tax revenue, the Sentani Samsat Office has implemented several policies and programs that have been made by the Papua Province Revenue Management Agency, including socialization, data collection and door-to-door billing, raids, and elimination of tax fines and sanctions for late payments.